Becoming a congenital heart surgeon: the long and challenging road. (19th October 2022) - Jacob, K A; Hussein, N; van Wijk, A; Heinisch, P P; Salih, C; Galetti, L; Hörer, J
Abstract: Training in congenital cardiac surgery is potentially lengthier and more demanding than training in any other surgical field. The duration of training is proportional to the complexity of the specialization. The expertise of a wide range of procedures is required. There is no doubt that some individuals may acquire the requisite abilities with greater ease than others, but fundamentally, these are capabilities that can be taught and learnt. Moreover, congenital cardiac surgeons are required to have a detailed understanding of pathophysiology and morphology, in addition to the stamina and empathy required to manage these complex patients. A fellowship is just the start of such training and is followed by a long road eventually leading to a lifelong journey to become a qualified congenital cardiac surgeon. Effective mentorship is a prerequisite throughout training to guide surgeons on this journey. Abstract : In 1938, the first congenital heart procedure was performed when Richard Gross ligated a persistent ductal arteriosus.